Religious Aspects in Hallstatt of Croatia - Potrebica, Hrvoje (Array, 1999)
The poster presents some characteristic religious and cult features of Hallstatt groups from the territory of Croatia. They can be seen on diverse parts of archaeological record, from ornaments on ceramics to burial ritual and grave inventories. Some of those features belong to the classic elements of Hallstatt cult (water birds and bovids), but other elements show clear influences of other cultures, especially Greek and Etruscan (tripods and other ceramic imitations of bronze vessels). Interesting features that are characteristic of some local groups also appear within the framework of Hallstatt groups. The poster will also present gender issues concerning cult, especially the role of women in the Hallstatt religious concept.